Penggunaan Media Pom-Pom Untuk Meningkatkan Kemampuan Mengenal Warna Pada Anak Usia 4-5 Tahun Di RA Arridwan Kecamatan Pakenjeng - Jubaedah, Endah; Setiawati, Euis (Jurnal Pendidikan Islam Anak Usia Dini : Anaking, 2024)
This research was conducted at RA Ar-Ridwan, Pakenjeng District, and identified several underlying issues, particularly related to color recognition. At the start of learning activities, some children were hesitant or unwilling to participate, opting instead to remain silent or cry, due to their inability to classify, group, and accurately identify colors. The objective of this study is to apply Pom-pom media at RA Ar-Ridwan to enhance children's color recognition skills, focusing on three indicators: classification, identification, and sequencing of colors. This study employs Classroom Action Research (CAR) using the Kemmis and Taggart model, which consists of four stages: planning, implementation, observation, and reflection. The subjects of this study included 10 respondents, comprising 4 male students and 6 female students. Based on the research findings, the color recognition ability of the children in the pre-cycle phase was at 20% for those who developed as expected and very well. This improved to 30% in Cycle I and further increased to 80% in Cycle II, indicating a significant enhancement in color recognition skills through the use of Pom-pom media. Keywords: Pom-pom media, ability, color recognitionKeywords: Recognizing Colors, Pom-Pom Media, Improvemen